A study of selected non-degree agricultural training institutions in the Western State of Nigeria - Butler, Robert O.; Consortium for the study of Nigerian rural development (East Lansing, Consortium for the Study of Nigerian Rural Development, Michigan State University, 1969)
The research project reported in this document was conducted as part of the Consortium for the Study of Nigerian Rural Development (CSNRD)
Bibliography: p. 158-159.
osc 26/08/2021
Arch
Keywords: Agricultural education; Nigeria